Defining the regulon of genes controlled by σE, a key regulator of the cell envelope stress response in Streptomyces coelicolor. Issue 2 (29th April 2019) - Tran, Ngat T.; Huang, Xiaoluo; Hong, Hee‐Jeon; Bush, Matthew J.; Chandra, Govind; Pinto, Daniela; Bibb, Maureen J.; Hutchings, Matthew I.; Mascher, Thorsten; Buttner, Mark J.
Summary: The extracytoplasmic function (ECF) σ factor, σ E, is a key regulator of the cell envelope stress response in Streptomyces coelicolor . Although its role in maintaining cell wall integrity has been known for over a decade, a comprehensive analysis of the genes under its control has not been undertaken. Here, using a combination of chromatin immunoprecipitation‐sequencing (ChIP‐seq), microarray transcriptional profiling and bioinformatic analysis, we attempt to define the σ E regulon. Approximately half of the genes identified encode proteins implicated in cell envelope function. Seventeen novel targets were validated by S1 nuclease mapping or in vitro transcription, establishing a σ E ‐binding consensus. Subsequently, we used bioinformatic analysis to look for conservation of the σ E target promoters identified in S. coelicolor across 19 Streptomyces species. Key proteins under σ E control across the genus include the actin homolog MreB, three penicillin‐binding proteins, two L, D‐transpeptidases, a LytR‐CpsA‐Psr‐family protein predicted to be involved in cell wall teichoic acid deposition and a predicted MprF protein, which adds lysyl groups to phosphatidylglycerol to neutralize membrane surface charge. Taken together, these analyses provide biological insight into the σ E ‐mediated cell envelope stress response in the genus Streptomyces . Abstract : The extracytoplasmic function (ECF) factor, σ E is a central regulator of the cell envelope stress response in Streptomyces coelicolor . Key proteins under σ E control include the actin homolog MreB, three penicillin‐binding proteins, two L, D‐transpeptidases, a LytR‐CpsA‐Psr‐family protein predicted to be involved in cell wall teichoic acid deposition, PspA, involved in the maintenance of membrane integrity, and a predicted MprF protein, which adds lysyl groups to phosphatidylglycerol to neutralize membrane surface charge.